(untitled) (Psychology Travelogs, 2024)
Over the past few years, the training of the specialists in Ukrainian high education is experiencing the new challenges. This is due to the current social crisis, but the difficult living conditions of citizens require quality and competent specialists in the field of pedagogy and psychology. The conditions for ensuring of professional competency are number of personal features, which relate to variety mental spheres. The main one is emotional-volitional sphere. The emotional stability is one of the important components in the structure of emotional-volitional sphere, which determines necessary level of stress tolerance and voluntary control. It was suggested that a low level of emotional stability not only reduces the professional ability to save optimal level of professional competency and work capacity in difficult working conditions. It determines number of interpersonal disorders, and it has a negative impact on professional activity of specialist in the system «person-person». The study was conducted to analyze interpersonal interaction of future educators and psychologists, depending on a level of emotional stability. It was found that people with high level of emotional stability are more likely to the confrontation in a conflict, and they less often make concession. If needed, they more often use a cooperation, but not a compromise or a concession. The emotional stability people select dominative styles of interpersonal communication. It is often the aggressive style of interpersonal interaction, and they seldom use the dependent and the subordinate styles. The emotional stability people are not afraid to defend their position, they aren’t prone to conformation. Therefore, the emotional stability is synonym of emotional balance. This is expressed in confident, independent behavior, ability to maintain the own boundaries and resist group pressure.